ADHERENCE AND PATHOGENICITY ASSAY OF VIBRIO HARVEYI IN TIGER SHRIMP (PENAEUS MONODON) LARVAE FOR SCREENING BIOCONTROL AGENT - ANTONIUS SUWANTO; YUSMINAH HALA; RIDWAN AFFANDI; MUHAMMAD ZAIRIN Jr. (BIOTROPIA, 2002)
Rifampicin-resistant marker was employed as a reporter to detect the adherence and colonization of V. harveyi  in shrimp larvae. Vibrio harveyi P1B  and YA32.2 were isolated from dead shrimp larvae in Besuki, Northern Coast of East Java, while V. harveyi HB3, was isolated from pristine sea water in Pacitan, Southern Coast of East Java. Vibrio metschnikovii used as biocontrol agent was isolated from healthy shrimp larvae in Serang, West Java. Spontaneous mutation was conducted to generate V. harveyi P1B, YA32.2 and HB3 resistant to rifampicin. These mutants exhibited similar survival ability to their parental (wild type) strains. Significant larval mortality was observed in shrimp larvae inoculated with YA32.2 than that of larvae inoculated with P1B. Larvae  inoculated with HB3 showed the lowest mortality. Bacterial cell count of Vibrio Rf*  in dead  larvae were 103-104 cells/larvae. Isolates of Vibrio metschnikovii Z and M as biocontrol candidates effectively reduced the growth and adherence ability of YA32.2 to shrimp larvae. Larval mortality in rearing water inoculated simultaneously with YA32.2 and V. metschnikovii was lower than the one inoculated with YA32.2 alone. Therefore, Vibrio metschnikovii Z or M could be developed as an effective probiotic or biocontrol agent for V. harveyi in shrimp hatcheries. Key words :   Biological control/Vibrio metschnikovii/shrimp \arvae/Penaeus mwu«fon/pathogenicity assay/Vibrio harveyi